The Paley-Wiener-Levinson theorem revisited - A. G. García (International Journal of Mathematics and Mathematical Sciences)
In this paper a new proof of the Paley-Wiener-Levinson theorem is presented. This proof is based upon the isometry between the Paley-Wiener space and that of the square-integrable functions in [−π,π], on one hand, and a Titchmarsh's theorem which allows recovering bandlimited, entire functions from their zeros, on the other hand.